Physiotherapy postgraduate studies in South Africa: Facilitators and barriers - Saul Cobbing; Stacy Maddocks; Simoene Govender; Shuaib Khan; Mpilonhle Mbhele; Kareena Naidoo; Summaya Tootla; Claire E. Weston (AOSIS, 2017)
Aim: To investigate the facilitators and barriers to attaining a postgraduate physiotherapy degree in South Africa. Methods: A quantitative, cross-sectional design using an internet-based survey was employed. The population of the study included all qualified physiotherapists who had completed community service and who were on the South African Society of Physiotherapy e-mailing list at the time of the study. Results: In all, 425 valid responses were received. The study participants were predominantly white women with a mean age of 36.9 and the majority were working in private practice. A total of 20.5% of respondents had completed a master's or doctoral degree in physiotherapy, while a further 13% of respondents were registered for a postgraduate degree in physiotherapy at the time of the study. Study participants who had obtained a postgraduate degree identified the same main barriers (namely cost/lack of financial support, family commitments and lack of time) and the same main facilitators (namely gaining of expertise, fulfilment of a personal goal and improvement of patient care) as participants who had not obtained a postgraduate degree. Participants who had not obtained a postgraduate degree were significantly more likely (p < 0.05) to report concerns regarding their own ability and a lack of motivation as barriers to further study. Conclusion: South African physiotherapists with and without a postgraduate degree reported common facilitators and barriers to pursuing postgraduate studies. In order to ensure that a greater number and diversity of physiotherapists see postgraduate studies as a worthwhile career option, stakeholders in health and education in both the South African public and private sectors need to be engaged to limit the barriers to postgraduate study and seek novel methods of making postgraduate study a more attractive option from a personal development and career perspective.